Pozzolanic Metakaolin Reactions: Stoichiometric and Kinetic Modeling - Kira Weise; Neven Ukrainczyk; Eduardus Koenders (Materials & Design, 2024)
In the pursue of environmentally-friendly binders for the construction industry, metakaolin (MK) has emerged as promising material, with its hardening performance primarily driven by pozzolanic reactions. However, in systems containing MK and calcium hydroxide (CH), transformation reactions from metastable to stable phases, particularly in excessive CH conditions, can adversely affect material properties. To anticipate these processes, this study introduces a stoichiometry-based reaction modeling approach for pozzolanic MK reactions, encompassing both short-term kinetics and long-term transformation processes. The primary pozzolanic reactions of MK are briefly outlined, highlighting two sequential, partially overlapping reactions forming C4AH13 and C2ASH8. Short-term reaction kinetics are modeled using isothermal calorimetry measurements and deconvoluting the two reaction peaks. The model is in good agreement with experimental quantitative X–ray diffraction (qXRD), thermogravimetric analysis (TGA) and helium pycnometer (density, i.e. solid volume) results. Model limitations are discussed based on qualitative scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDX) analysis. Leveraging the proposed model, the temperature dependency of pozzolanic MK reactions is analyzed, revealing an activation energy for the primary reaction of 84 kJ/mol. The model is intended to lay a foundation for designing innovative binder systems based on metakaolin, while paving the way for sustainable construction in the future.